Jealousy Protest to a Social Rival Compared to a Nonsocial Rival in Chilean Infants 10–20 Months Old - Fernandez-Tapia, A; Baeza-Ugarte, C (John Wiley and Sons Inc, 2022)
Jealousy protests have been linked to the intrusion of social rivals challenging infants exclusive access to maternal care and resources that typically accompany attachment. Previous studies revealed that the experimental presentation of social rivals evokes protest in as early as 6 months old infants. This study replicated research on jealousy protests in a novel language and sociocultural context with 10–20 months old infants. We compared protests of 45 children when their mothers attended to each of the rivals and controlled for attachment dimensions. As hypothesized, infants had a stronger jealousy protest to the social rival, and their response was associated with attachment avoidance. We concluded that our results contribute to evidence on jealousy protest as an evolutionary rooted phenomenon that favors the mother s attention in a social rivalry scenario over nonsocial stimuli. Attachment avoidance may be a precluding factor of jealousy when faced with a social rival scenario that deserves further research. © 2022 International Congress of Infant Studies.